Commons of Identity: Sherpa Identity Management - Loland, Leif Rune (Dhaulagiri Journal of Sociology and Anthropology, 2006)
The recent history of Sherpas demonstrates how identities can be scarce goods. While ‘Sherpa’ refers to an ethnic identity, ‘Sherpa’ refers to a crucial occupation in the trekking industry.i Their privileged position in Nepal’s international tourist industry is related to their common reputation. Their collective use of identity seems to help them getting access to an economic niche, and work in tourism seems to be an aspect of being Sherpa. Thus, an individual that operates in the tourist market does not only manage material assets but also identity assets to maintain the Sherpa reputation. Consequently, one can expect it to be a collective concern to husband their image, ie to control each member’s behaviour which could affect the Sherpa image. This article on Sherpa identity in encounters with outsiders analyses Sherpaness as a manageable resource that constitutes a collectively sanctioned commons. My point of departure is Barth’s analysis of ethnic boundary dynamics (1969, 1994) combined with Bourdieu’s concept of ‘capital’ and Hardin’s perspective on commons. DOI: 10.3126/dsaj.v1i0.288 Dhaulagiri Vol.1 (2005) pp.176-192